IMPLEMENTASI USER EXPERIENCE DESIGN PADA PERANCANGAN APLIKASI PEMBELAJARAN PRAKTIKUM ONLINE BERBASIS MOBILE - Eri Haryanto; Agustin Setiyorini (Universitas Janabadra, 2022)
The online practicum learning media must of course be in the form of an information system that can be easily accessed by practicum teachers and practicum participants. When there are many learning platforms that can be obtained easily, but are not sufficient to accommodate practical lecture activities. So that laboratory managers need to develop practical learning applications that are easy for users. In this research, the application of User Experience Design (UX Design) will be carried out on online practicum learning applications based on the results of functional testing of the application using several trials, the application functions well and can be used. By designing the user experience design, it is easier for application users to use the applications that are built.. Keywords: user experience design, online practicum, aplikasi praktikum, UXD